Dynamics of Problem of Asset Forfeiture of Corruption Proceeds and the Concept of Its Law Enforcement - mahmud, ade (Jurnal Wawasan Yuridika, 2023)
Forfeiture of assets from corruption crime has not shown signifi cant results in termsof assets returned; in fact, the value of assets returned is smaller than state losses. Thisstudy aims to explain the dynamics of the problem of asset forfeiture due to corruptioncrimes and the concept of eff ective law enforcement to seize assets resulting fromcorruption. The specifi cation of the research is descriptive with normative juridicalresearch type, using a statutory and conceptual approach based on secondary datacollected by documentation study technique, and analyzed qualitatively withoutapplying formulas and numbers. The results of the study show that the state hasdiffi culty seizing assets resulting from corruption crimes since the assets placedabroad have been transferred to other parties and the restitution has not been paid.The concept of eff ective law enforcement is to track assets, apply restitution withouta subsidiary, which is preceded by blocking and forfeiting assets, and carry outexecutions through auctions, with the proceeds going to the state treasury.